Tracking Science: An Alternative for Those Excluded by Citizen Science. (3rd March 2021) - Liebenberg, Louis; //Ao, /Am; Lombard, Marlize; Shermer, Michael; Xhukwe, /Uase; Biesele, Megan; //xao, Di; Carruthers, Peter; Kxao, ≠Oma; Hansson, Sven Ove; Langwane, Horekhwe (Karoha); Elbroch, L. Mark; et al.
In response to recent discussion about terminology, we propose "tracking science" as a term that is more inclusive than citizen science. Our suggestion is set against a post-colonial political background and large-scale migrations, in which "citizen" is becoming an increasingly contentious term. As a diverse group of authors from several continents, our priority is to deliberate a term that is all-inclusive, so that it could be adopted by everyone who participates in science or contributes to scientific knowledge, regardless of socio-cultural background. For example, current citizen science terms used for Indigenous knowledge imply that such practitioners belong to a sub-group that is other, and therefore marginalized. Our definition for "tracking science" does not exclude Indigenous peoples and their knowledge contributions and may provide a space for those who currently participate in citizen science, but want to contribute, explore, and/or operate beyond its confinements. Our suggestion is not that of an immediate or complete replacement of terminology, but that the notion of tracking science can be used to complement the practice and discussion of citizen science where it is contextually appropriate or needed. This may provide a breathing space, not only to explore alternative terms, but also to engage in robust, inclusive discussion on what it means to do science or create scientific knowledge. In our view, tracking science serves as a metaphor that applies broadly to the scientific community—from modern theoretical physics to ancient Indigenous knowledge.